Investigating university students' colloquial speech utterances of English in intercultural settings: a case study in Albanian context - Flett Klosi, Dorjana (European Scientific Journal, ESJ, 2024)
In today's world, the widespread use of English, along with student mobility, democratisation, cultural diversity, and the influence of media—especially the Internet—shapes the language environments of higher education institutions from a broad cultural and international communication perspective. This situation is also evident at the University "Ismail Qemali" in Vlore, Albania. The author of this paper researched how English is utilized by both local and foreign students outside the classroom. To gather data, informal conversations were recorded and systematically analyzed using descriptive approaches, statistical modeling, and conversation analysis methods, involving a corpus of 60 students from different native backgrounds (47 local Albanian students and 13 European students). Qualitative and quantitative data were collected to identify phonetic patterns, their occurrences in colloquial speech, and the reasons behind certain linguistic usages or deviations observed in students' "small talk" in multicultural settings. Some participants noted that they are influenced by English and American cultures and lifestyles to varying degrees. Conversely, other students communicated in their native languages while applying basic speech acts that were typical of their original cultural backgrounds. This behaviour illustrated some inconsistencies in phonetics, grammar, and vocabulary. These linguistic deviations reflect how language embodies individual personalities and cultural backgrounds, as speakers adapt their styles and settings in conversation.